The diagnostic efficacy of combining bronchoscopic tissue biopsy and endobronchial ultrasound‐guided transbronchial needle aspiration for the diagnosis of malignant lesions in the lung. Issue 11 (23rd February 2012) - Schwartz, Lauren Ende; Aisner, Dara L.; Baloch, Zubair w.; Sterman, Daniel; Vachani, Anil; Gillespie, Colin; Haas, Andrew; Litzky, Leslie A.
<x xml:space="preserve">Abstract</x> Bronchoscopic tissue forceps biopsy (BBX) is a standard procedure for diagnosis of malignancy in the lung. Endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) has proven to be a sensitive alternative to tissue biopsy for the diagnosis and staging of lung tumors. We report our institutional experience with diagnostic yield when combining BBX and EBUS‐TBNA in the bronchoscopic evaluation of patients presenting with lung lesion(s). The pathology files at our institution were searched for all patients who underwent combined BBX and EBUS‐TBNA procedures between 1/09 and 6/10 for the diagnosis of malignancy. The data points included biopsy site, cytologic, and histopathologic diagnoses and follow‐up. We identified 115 patients who underwent BBX combined with EBUS‐TBNA. About 107 (93%) of the patients received a definitive pathologic diagnosis; 93 (81%) were malignant. BBX and EBUS‐TBNA of the lung lesion only were performed in 21 patients, BBX and EBUS‐TBNA of lymph node(s) only in 78 patients with BBX and a combination of EBUS‐TBNA of the lung lesion and lymph node(s) in 16 patients. Immunostains were performed for 71 (76%) patients and molecular testing for 11 (12%) patients. Diagnostic yield is increased when bronchoscopic technologies are combined. In a significant number of patients where BBX was negative, EBUS‐TBNA provided diagnostic material, increasing diagnostic yield by 18%. In a subset of these patients the EBUS‐TBNA assisted in the staging of a primary tumor. By combining these procedures, more tissue was obtained for immunohistochemistry and molecular testing, which facilitated personalized management in a minimally invasive manner. Diagn. Cytopathol. 2013;41:929–935. © 2012 Wiley Periodicals, Inc.